The Effect of Kepok Banana Skin Liquid Organic Fertilizer (Musa paradisiaca) on the Growth of Mustard Plants (Brasicca juncea L.) - Isherdini, I; Athena, Berliana Putri; Suparti, S (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
Green mustard (Brassica Juncea L.) is a vegetable that contains a lot of vitamins and high nutrients, so mustard greens have high commercial value and marketing prospects. Mustard greens are also much liked by the public for consumption, therefore the level of market demand for mustard lants is very high. The production of mustard greens in Indonesia is still not optimal to meet market demand, therefore a research is being carried out on applying Liquid Organic Fertilizer (POC) t mustard greens. There were 4 different experimental treatments in this study. This study used an experimental method, namely by using a Completely Ranomized Design (CRD) using 2 treatment factors. The first treatment factor is the volume of Liquid Organic Fertilizer (POC) watering and the second treatment factor is the time of Liquid Organic Fertilizer (POC) administration. P0 = control, P1 = 10 ml POC, P2 = 15 ml POC, P3 = 20 ml POC and P4 = 25 ml POC. The results of the study stated that the best for P4 treatment.